OPTIMALISASI WEBSITE MELALUI PENERJEMAHAN KONTEN TRILINGUAL SEBAGAI UPAYA UNTUK PENINGKATAN JUMLAH WISATAWAN - Dyah Raina Purwaningsih; Tri Wahyu Setiawan Prasetyoningsih; Dian Bayu Firmansyah (Jurnal Pengabdian Kepada Masyarakat Patikala, 2022)
The increasing growth of tourism by both local and foreign tourists requires a thorough integration of tourist attractions in Banyumas through appropriate and attractive promotional tools to increase the number of local and foreign tourists visiting. Tourism promotion tools provide objective information as a guide for potential tourists regarding location, transportation access, accommodation, and the costs needed to get to the attraction. The media can be digital, such as tourist content on official government or private pages. This service activity aims to introduce tourist destinations around the Banyumas area through digital media in the form of web content in three languages, Indonesian-English-Japanese. With the availability of these promotional tools, prospective tourists can receive objective information related to Banyumas tourist destinations, thereby encouraging an increase in the number of tourists visiting Banyumas.